Strategi Bersaing untuk Mengoptimalkan Kapasitas Produksi: Studi Kasus pada PT. Jaya Indah Casting, Bekasi - Purwanto Purwanto (The Winners, 2011)
Every company has to be able to adapt with the environment in order to survive in the middle of the condition as mentioned. Therefore, the management is supposed to manage their organization in a good manner and more professional to plan and control the company’s activities. PT. Jaya Indah Casting as a multinational company is selected as a study case for a research that aims to analyze the external and internal business environment; identify and evaluate business strategic implemented; find the future alternative strategic to be implemented by the company. The external business environment is analyzed by common business environment (economic, political, ecology and technology), Porter’s competitive forces, driving forces and key success factors. The internal business environment will be analyzed by SWOT method, organization structure, financial reports, process mapping, contingency plan and benchmarking, which altogether will be combined to formulate business strategic for the future. Results show that to survive the development and win the competition, PT. Jaya Indah Casting should implement growing strategic, operational strategic (new field and new product, new customer, quality and customer satisfaction), location and machine/tools maintenance.